Implementation and control of a magnetically coupled 'cuk converter with damping network for optimal battery charging - Agarwal A.; Singh R.K. (My University, 2025)
The objective of this paper is to implement and control a modified magnetically coupled 'Cuk converter for the optimal charging of a battery. The paper shows how simple modifications in the bidirectional magnetically coupled 'Cuk converter results in a converter that exhibits a fifth order minimum phase behaviour for both buck and boost operation. With the use of a novel feedback clamped controller, the converter is tested for the optimal bidirectional battery charging applications. Steady-state and dynamic analysis of the derived converter is also described. Experimental and simulation results are presented to verify the proposed algorithm.